Pelaksanaan Home Visit dalam Penyelesaian Masalah Kemalasan Mengaji Anak-anak di Nagari Sungai Tunu Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan - Wenpa Sulaini; Afnibar Afnibar; Jemkhairil Jemkhairil (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2023)
Learning to recite the Al-Qur'an for children is an obligation. For some children, reciting the Al-Qur'an is a boring activity and difficult to understand. In Nagari Sungai Tunu, there are children who show laziness, such as going home early, and have been reading the Al-Qur'an for a long time without reading fluently. One of the programs carried out by TPQ for lazy children is home visit. In general, after a home visit is carried out, lazy children appear to start diligently studying the Al-Qur'an. Researchhers want to see in more detail and comprehensively the implementation of home visit carried out by Al-Qur'an teachers.